TEMPUNG MATEI BILEI: SALAH SATU DELIK ADAT REJANG LEBONG DI BENGKULU - Lestari, Putri; Istaviolani, Silva; Rahmadhani, Rizki Ayu; Perdinan, Perdinan; Yana, Sumayah Fitri (Cahaya Ilmu Bangsa, 2025)
Tempung Matei Bilei is a traditional tradition that has deep meaning in the lives of the Bengkulu community, especially Rejang Lebong Regency. This ceremony functions as a means to honor ancestors, strengthen social ties, and preserve local culture. This journal discusses the understanding, implementation, meaning, and challenges in preserving Tempung Matei Bilei, as well as recommendations for maintaining its sustainability in the future. The purpose of the study is to determine the cultural value system of the Rejang Lebong community related to the implementation of Tempung Matei Bilei and also to determine the influence of tempung batei bilei on the social conditions of the community in Rejang Lebong. This article will use a qualitative approach and the type of research is a literature review. Data sources use secondary data from published research results, online media coverage, scientific journals, books, and documents that are related to the problems in this study. The data obtained will be analyzed using a descriptive method. Tempung Matei Bilei adalah tradisi adat yang memiliki makna mendalam dalam kehidupan masyarakat Bengkulu khususnya Kabupaten Rejang Lebong. Upacara ini berfungsi sebagai sarana untuk menghormati leluhur, memperkuat ikatan sosial, dan melestarikan budaya lokal. Jurnal ini membahas pengertian, pelaksanaan, makna, serta tantangan dalam pelestarian Tempung Matei Bilei, serta rekomendasi untuk menjaga keberlanjutannya di masa depan. Tujuan Penelitian ntuk mengetahui sistem nilai budaya masyarakat Rejang Lebong yang berkaitan dengan pelaksanaan Tempung Matei Bilei dan juga untuk mengetahui pengaruh Tempung Matei Bilei terhadap kondisi sosial masyarakat di Rejang Lebong. Artikel ini akan menggunakan pendekatan kualitatif dan jenis penelitian adalah kajian literatur. Sumber data menggunakan data sekunder dari hasil penelitian yang dipublikasikan, pemberitaan media daring, jurnal ilmiah, buku- buku, dan dokumen yang memiliki keterkaitan dengan masalah pada penelitian ini. Data yang diperoleh akan dianalisis menggunakan metode deskriptif.